Evaluating time until ligation in a novel tourniquet: a crossover randomized-controlled trial - Katzenschlager, Stephan; Schneider, Niko; Weilbacher, Frank; Weigand, Markus A.; Popp, Erik (The American journal of emergency medicine, 2024)
Introduction and aim - Severe external hemorrhage is a significant reason for morbidity and mortality in adults; thus, the swift and correct application of a tourniquet by laypersons can be lifesaving. We conducted this randomized-controlled cross-over study to investigate the use of a novel tourniquet. - Methods - Participants were recruited at the Heidelberg University Hospital. Eligible participants were ≥ 18 years old with a medical background but without prior experience in applying a tourniquet. Participants were 1:1 randomized to the intervention group (PAX tourniquet) or the control group (SAM or CAT tourniquet). In the control group, participants underwent another randomization to either the SAM or CAT tourniquet without a predefined allocation ratio. Hyperspectral measurements were undertaken (i) before ligation, (ii) 30 s after ligation, and (iii) 30 s after the reopening of the tourniquet. The primary outcome was time until ligation before crossover between the respective groups. The analysis of secondary endpoints included all attempts to assess a possible learning effect, intraoperator variability, and hyperspectral measurements. Participants were crossed to the other study group after a brief wash-out phase. - Results - In total, 50 participants were recruited, resulting in 100 attempts. A success rate of 98% was observed across the study population. Time until ligation was 49 s and 56 s (p = 0.572) in the intervention and control group, respectively. However, there was a significant difference between the PAX and SAM (54 vs 75 s; p = 0.037) and the SAM and CAT tourniquet (75 vs. 47 s; p = 0.015). Further, we observed a significant learning effect in participants allocated to the control group first, with a median reduction of 9 s in the time until ligation. Hyperspectral measurements showed a significant decrease in perfusion and tissue oxygenation after ligation. Further, a significant increase in perfusion and tissue oxygenation was found after reopening the tourniquet compared to the baseline measurement. - Conclusion - The novel PAX tourniquet can be applied quickly and effectively by medical personnel without prior experience in applying a tourniquet.